Predictors of sleeping under cost-free mosquito bed nets among children under-five years in Mbarara, Uganda: a household survey - Andinda, Maureen; Mulogo, Edgar; Turyakira, Eleanor; Batwala, Vincent (African Health Sciences, 2019)
In 2010, Uganda Malaria Control Programme distributed cost-free mosquito bed nets to households with children under-five years and pregnant women in selected sub-counties. We assessed the factors associated with sleeping under costfree mosquito nets among children under-five years in Nyakayojo sub-county, Mbarara District, Uganda. Methods: 381 households with at least a child under-five years and benefited from cost-free bed nets in Nyakayojo were randomly selected. Caregivers of children were interviewed using a questionnaire. Results: 74% children slept under bed nets a night before the study. Children from households with ≥2 nets [aOR=1.75; 95% CI: 1.09-2.81, p=0.02], female caregiver [aOR=2.11; 95% CI: 1.16-3.79, p=0.01] and children from households that did not face problems (skin irritation, torn nets, suffocation, night sweating, nasal congestion and candle fire) when sleeping under bed nets [aOR=1.81; 95% CI: 1.10-2.98, p=0.02] were more likely to use nets. Main reason for not sleeping under a net was damage to the net (47.1%). Conclusion: The proportion of children sleeping under nets was comparable to MDG target. Improvements in use of mosquito nets by children can be achieved through increasing number of nets in a household.
Keywords: Cost-free; mosquito nets; use; under-five; Uganda